Acute gastrointestinal bleeding: proposed study outcomes for new randomised controlled trials - Jensen, Dennis M. (2022)
Acute gastrointestinal bleeding (GIB) remains a common cause of hospitalisation. However, interpretation and comparisons of published studies in GIB have been hampered by disparate study methodology.